Proceedings of the Regional Meeting on the Establishment of Co-operative Programmes of Interdisciplinary Ecological Research - Regional Meeting on the Establishment of Co-operative Programmes of Interdisciplinary Ecological Research, Tarining and (1975 Sfax); Programme on Man and the Biosphere; Programme on the Ecological Management of Arid and Semi-arid Rangelands in Africa and the Near and Middle East (EMASAR) of FAO (Paris : Unesco, 1975)
01